2016
DOI: 10.1073/pnas.1605738113
|View full text |Cite
|
Sign up to set email alerts
|

Search for supersolidity in solid 4 He using multiple-mode torsional oscillators

Abstract: In 2004, Kim and Chan (KC) reported a decrease in the period of torsional oscillators (TO) containing samples of solid 4 He, as the temperature was lowered below 0.2 K Science 305(5692) :1941-1944]. These unexpected results constituted the first experimental evidence that the long-predicted supersolid state of solid 4 He may exist in nature. The KC results were quickly confirmed in a number of other laboratories and created great excitement in the low-temperature condensed-matter community. Since that time, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In 1970, Leggett used Eq. 4 and the known information on the helium lattice to estimate f s < 10 −4 for solid helium (10), a result compatible with current measurements (17). Our dipolar supersolid does not move in a 1D configuration as in the Leggett model but has a more complex dynamics in the whole (x,y) plane, with both motion along the x axis, where the density modulation forms, and rotation of the individual droplets.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In 1970, Leggett used Eq. 4 and the known information on the helium lattice to estimate f s < 10 −4 for solid helium (10), a result compatible with current measurements (17). Our dipolar supersolid does not move in a 1D configuration as in the Leggett model but has a more complex dynamics in the whole (x,y) plane, with both motion along the x axis, where the density modulation forms, and rotation of the individual droplets.…”
supporting
confidence: 89%
“…The original announcement of the possible presence of a large superfluid fraction, f s ≈ 10 −1 (13,14), later received a different interpretation based on a change of the elastic properties of the solid (15) and has not been confirmed by more recent studies (16). Superfluidity in bulk solid helium has now been excluded down to the level of 10 −4 (17), and the search goes on in two-dimensional (2D) films (18).…”
mentioning
confidence: 99%
“…This is in contrast to what is observed with a real superfluid, in which the relative response, or superfluid density, is frequency independent. A series of measurements with multimode torsional oscillators, confirmed that most, if not all, of the observed period shifts were due to changes in the shear modulus of the solid (35). Thus, the beautiful dream of the supersolid dies.…”
Section: Retirement and The Supersolid Debate 2004-presentmentioning
confidence: 78%
“…While there is still current interest in the search for supersolidity in 4 He [148,300,301], atomic BECs started to garner theoretical interest in the early 2000s. Various proposals for systems which might display supersolid behaviour were made, including laser induced electrostriction [302], dipolar gases [303][304][305], and atoms weakly coupled to Rydberg states [306].…”
Section: Supersolidsmentioning
confidence: 99%